Chinese Foreign Direct Investment in France: Motivations and Management Style - Gao, Ni; Schaaper, Johannes (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2018)
This research investigates the main motivations driving China’s foreign direct investment (FDI) in France and the management style that Chinese companies adopt toward their French subsidiaries. On the basis of interviews with managers of 17 Chinese subsidiaries in France, the authors identify sales in French and European markets as the main driver of Chinese FDI in France. Chinese FDI in France also aims at building bridges to African markets. The second FDI motive is asset seeking. For managing their subsidiaries in France, the Chinese companies adopt a polycentric management style. The Chinese parent companies rely on French managers, while Chinese expatriates adopt observational attitudes. This research confirms that the Chinese government is closely involved in Chinese outward FDI and supports both the “linkage, leverage, and learning” perspective and springboard theory.